Disseminated melioidosis in early pregnancy - an unproven cause of foetal loss - Chang, Chee; Lau, Nina Lee Jing; Currie, Bart J.; Podin, Yuwana (Springer Nature, 2020)
Abstract Background: Melioidosis is a potentially life-threatening infection caused by the Gram-negative bacterium Burkholderia pseudomallei. Melioidosis is difficult to diagnose due to its diverse clinical manifestations, which often delays administration of appropriate antibiotic therapy. Case presentation: Melioidosis is uncommon in pregnancy but both spontaneous abortion and neonatal melioidosis have been reported. We report a case of bacteraemic melioidosis in a young woman with a subsequent spontaneous abortion, with B. pseudomallei cultured from a high vaginal swab as well as blood. Conclusion: It remains unclear in this and previously reported cases as to whether the maternal melioidosis was sexually transmitted. Keywords: Melioidosis, Burkholderia pseudomallei, Pregnancy, Abortion